Co‐selection for antibiotic resistance genes is induced in a soil amended with zinc. (9th October 2019) - Tongyi, Yang; Yanpeng, Liu; Xingang, Wang; Fen, Yang; Jun, Lu; Yubin, Tang
Abstract: The likelihood of co‐selection for antibiotic resistance induced by heavy metals is a potential threat to human health, however, direct evidence of heavy metal‐induced co‐selection of antibiotic resistance is lacking in soil. By using a metagenomic sequencing approach, zinc (Zn) driven co‐selection of antibiotic resistance genes (ARGs) in soil was investigated through a microcosm experiment where Zn salts were added at different levels. The results showed that the abundance and diversity of ARGs had a tendency to increase along the gradient of increasing Zn contents, with the maximum values recorded in the soil amended with 800 mg Zn kg −1 . The abundance of mobile genetic elements (MGEs) such as integrons and insertion sequences was significantly increased by Zn exposure. Network analysis demonstrated significant associations between ARGs and MGEs, suggesting that Zn treatment might enhance the potential for horizontal transfer of ARGs. Furthermore, structural equation models revealed that the types of ARGs were primarily driven by variations in bacterial compositions and Zn exposure, followed by integrons. Thus, these results indicate that added Zn salts considerably changed the diversity, abundance and mobility potential of antibiotic resistance, and imply that application of amendments containing high levels of Zn to soil could be causing the emergence and release of ARGs to the environment, and should be carefully monitored.